Kolaborasi Pentahelik Pengelolaan Desa Wisata di Kabupaten Batang - Dwi Edi Wibowo; Agung Aditya; Aditya Migi Prematura; Mutimatun Ni'ami (UNES Law Review, 2024)
Tourist villages in Batang Regency, Central Java, have great potential for development through pentahelix collaboration. Although collaborative efforts have been made, challenges such as inter-party coordination and marketing strategies still need improvement. The purpose of this research is to analyze the form of pentahelix collaboration in the management of tourist villages in Batang Regency and to identify supporting and hindering factors that affect this collaboration. This study uses empirical legal methods to analyze pentahelix collaboration in the management of tourist villages in Batang Regency through in-depth interviews, direct observation, and qualitative analysis. The results show that pentahelix collaboration in the management of tourist villages in Batang Regency involves the integration of five main components: government as facilitator and regulator, local communities as the main drivers, academics contributing through research, the business sector providing capital and expertise, and media playing a role in promotion. The implementation of this collaboration is evident in various tourist village development programs. The main supporting factors include local government commitment, active community participation, academic contributions, business sector investment, and the media's role in promotion. However, there are several obstacles such as lack of coordination between elements, limited human resource capacity, limited access to funding, overlapping regulations, environmental sustainability challenges, and resistance to change.